Assessing the Competitiveness of the Malaysian Palm Oil Industry - Subramaniam, Devagi (1997)
Malaysia has been the world's largest producer and exporter of palm oil for the last fifteen years. The palm oil is facing stiff competition from other palm oil producers especially Indonesia. Indonesia's production of palm oil is increasing rapidly at more than 10% annually compared to Malaysia which showed an average growth of only 8.2% from 1990 to 1995. In response the Malaysian government has taken many efforts to improve the performance of the local palm oil industry. Despite the efforts of the government as well as the private sector to develop the palm oil industry in Malaysia, the performance of the industry, measured in terms of market share and profitability, is declining relative to those of other countries especially Indonesia. Therefore, the aim of this study is to assess the competitiveness of the Malaysian palm oil industry and to identify the factors affecting it.This study analyzed the competi1iveness of the pahn oil industry at the country and industay level The compcIitivmess at country level was detennincd by palm oil export performance which was measured by 1he constant Market Share model (CMS). The CMS model decomposes the export of palm oil into three effects ie. size of market, distribution and competitive effects. The result of the CMS analysis for the size of market effect shows that the country was unable to cope with world palm oil demand in the later periods, compared to Indonesia. The distribution effect showed that both Malaysia '8 and Indonesia '8 palm oil expolls were concentrated in markets where demand was growing at slower rates during earlier periods fonowed by faster rates in the later periods. Finally, the competitive effect showed a decline in Malaysia' 8 market share for the later periods, while Indonesia's market share was increasing continuously. Thus, Malaysia is graduaJly losing its competiJiveness to Indonesia in tenns of market share. The analysis was carried out on crude palm oil (CPO) millers. The perfonnance of the industry was found to be affected by productivity, technology, market share, quality, balgaining power and cost of production. Performance was measured by value added and return on assets. The coefficient of determination was 64.0% and 42.08% for ROA and value added rcspec1ively. The results showed that the cost of production, market share, productivity of capital, quality (free fatty acid content) and technology were significant at 5%. Bargaining power did not contribute much to the performance of CPO millers. In conclusion, it was found that the competitiveness of the industry can be improved if the firms increase their production, productivity, technology, market share and reduce the cost of production.